Association of maternal serum total homocysteine level with gestational diabetes mellitus - Haider, Chowdhury Afsana; Islam, M. Mushfiqul; Fatema, M. Muhtarema; Nesa, M. Karimatun; Khan, Farzana Farhin; Ripa, Halima Jahan; Ahmed, Naorin; Eva, Nusrat Jahan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Gestational diabetes mellitus (GDM) is diabetes first diagnosed during pregnancy, affecting a significant proportion of pregnancies worldwide. This study was conducted to determine the association between maternal serum total homocysteine levels and GDM. The aim of the study was to evaluate the association between maternal serum total homocysteine levels and the occurrence of gestational diabetes mellitus. Methods: This case-control study was conducted in the Department of Obstetrics and Gynecology, Institute of Child and Mother Health (ICMH), Matuail, Dhaka, Bangladesh, from October 2023 to March 2025, including 36 pregnant women with GDM and 36 matched controls. Demographic, obstetric, and biochemical data, including serum total homocysteine (Hcy) levels measured by ELISA, were collected, and associations with blood glucose were analyzed using SPSS 27.0; GDM was diagnosed per WHO (2013) criteria and elevated Hcy defined as ≥6.38 µmol/l. Results: Among 72 pregnant women, mean serum total homocysteine was higher in GDM cases than controls (9±3.5 vs. 6.7±3.7 µmol/l, p=0.008). Women with homocysteine ≥6.38 µmol/L had 4.55 times higher odds of GDM (95% CI: 1.69-12.25, p=0.003). Homocysteine levels correlated positively with fasting blood sugar (r=0.543, p<0.001) and 2-hour post-75g glucose (r=0.388, p=0.001). Conclusions: This study establishes that elevated maternal serum total homocysteine levels are associated with gestational diabetes mellitus and may serve as a potential biomarker for GDM risk.